Application of glyphosate doses in different phenological stages of soybean culture (Research, Society and Development, 2020)
The present study aimed to evaluate the influence of glyphosate on the RR soybean crop using doses of glyphosate at different phenological stages. Thus, an experiment was carried out in a randomized block design, in a 4x4 factorial scheme, with treatments consisting of the combination of four doses of glyphosate (0; 2; 4; 6 L / ha), applied in four phenological stages (V2, V4, V6 and V8), vegetative of soy, with 4 repetitions. The cultivar used was DM 66I68 RSF IPRO. The variables analyzed were plant height and first pod insertion, stem diameter, number of pods per plant, number of grains per pod, mass of 1000 grains and grain yield. The data for the glyphosate doses were submitted to regression analysis and the data for phenological stages were subjected to the Tukey test at the level of 5% of significance. Regardless of the phenological stage of the soybean crop, the use of glyphosate does not negatively affect the height of insertion of the first pod, stem diameter and mass of 1000 grains. It is recommended to apply glyphosate to the phenological stage V4 of the soybean crop. After this stage, the herbicide has a negative effect on the number of grains per pod and grain yield.